2009
DOI: 10.1002/jid.1587
|View full text |Cite
|
Sign up to set email alerts
|

Pushing lenders to over‐comply with environmental regulations: A developing country perspective

Abstract: In the past few years, the number of lenders adopting voluntary environmental codes, such as the Equator Principles, is increasing. The main reasons for this form of over-compliance include warm glow preferences of agents, credit risk and incentives arising from regulation. Empirical evidence suggests that lenders that over-comply are generally bigger than those that don't. In particular, they are likely to be MNCs. In addition, the behaviour of over-complying lenders differs from other lenders, for instance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…For the countries assigned to low ECRM performance in Figure , both the voluntary code and green income incentive have low influence. This indicated that the voluntary codes do not have much influence in developing areas because there is less reason for complying such as regulatory environment in these areas (Kulkarni, ). Such regions also lack green income incentive to make banks' performance better in ECRM.…”
Section: Resultsmentioning
confidence: 99%
“…For the countries assigned to low ECRM performance in Figure , both the voluntary code and green income incentive have low influence. This indicated that the voluntary codes do not have much influence in developing areas because there is less reason for complying such as regulatory environment in these areas (Kulkarni, ). Such regions also lack green income incentive to make banks' performance better in ECRM.…”
Section: Resultsmentioning
confidence: 99%
“…Reputation appears to be more important for multinational companies, as they face more stakeholder pressure. CSR issues are thus essential for the global players being in the spotlight (Kulkarni , p. 475). By adopting the EPs as a transnational CSR initiative, Equator banks take preventative and proactive measures to protect their reputation and defend themselves against civil society activism and NGO reputational pressure.…”
Section: Bridging the Gap: People Planet And Profitmentioning
confidence: 99%
“…This “two‐speed” or “clubs within the club” structure would allow Equator banks to proactively respond to social‐environmental and human rights issues and meet the demands of various stakeholder groups. Equator Principles Financial Institutions would have the strategic opportunity to “over‐comply” (Kulkarni ), to go beyond what is formally (legally) and informally (morally) required, and gain first‐mover (competitive) advantages. They might boost their credibility for environmentally and socially friendly business practices and as a consequence, gain (additional) reputational capital that directly adds to their brand value.…”
Section: Ep Iii: What Remains To Be Done?mentioning
confidence: 99%
See 1 more Smart Citation
“…This "two-speed" or "clubs within the club" structure would allow Equator banks to proactively respond to social-environmental and human rights issues and meet the demands of various stakeholder groups. Equator Principles Financial Institutions would have the strategic opportunity to "over-comply" (Kulkarni 2010), to go beyond what is formally (legally) and informally (morally) required, and gain first-mover (competitive) advantages. They might boost their credibility for environmentally and socially friendly business practices and as a consequence, gain (additional) reputational capital that directly adds to their brand value.…”
Section: Reform Steps 27mentioning
confidence: 99%